If x =
![(3 \: + \: \sqrt{8} ) (3 \: + \: \sqrt{8} )](https://tex.z-dn.net/?f=%283+%5C%3A++%2B++%5C%3A++%5Csqrt%7B8%7D+%29)
Show that
![( \: {x}^{2} + \: \frac{1}{ {x}^{2} } \: ) \: \: = 34 ( \: {x}^{2} + \: \frac{1}{ {x}^{2} } \: ) \: \: = 34](https://tex.z-dn.net/?f=%28+%5C%3A++%7Bx%7D%5E%7B2%7D++%2B++%5C%3A+++%5Cfrac%7B1%7D%7B+%7Bx%7D%5E%7B2%7D+%7D++%5C%3A+%29+%5C%3A++%5C%3A++%3D+34)
Answers
Answered by
2
★Ello ★
here is your answer !!
x = 3 + ✓8
there fore ,
1 /x = 1 / 3 + √ 8 × 3 -✓8 / 3 - ✓ 8
{ rationalize. }
1 / x = 3 -✓8 / 9 -8
=> 1 / x = 3 -✓ 8 / 1
now ,.
x + 1 / x => 3 + √ 8 + 3 - ✓ 8
=> x + 1 / x = 6
=> (x + 1 / x )² = x² + 1 / x² + 2 × x × 1 / x
=> ( 6 )² = x² + 1 / x² + 2
x² + 1 / x² = 36 -2
=> x² + 1/ x² = 34 .
hence proved !!!
hope it helps you dear !!
thanks !!
![thanks thanks](https://tex.z-dn.net/?f=thanks)
here is your answer !!
x = 3 + ✓8
there fore ,
1 /x = 1 / 3 + √ 8 × 3 -✓8 / 3 - ✓ 8
{ rationalize. }
1 / x = 3 -✓8 / 9 -8
=> 1 / x = 3 -✓ 8 / 1
now ,.
x + 1 / x => 3 + √ 8 + 3 - ✓ 8
=> x + 1 / x = 6
=> (x + 1 / x )² = x² + 1 / x² + 2 × x × 1 / x
=> ( 6 )² = x² + 1 / x² + 2
x² + 1 / x² = 36 -2
=> x² + 1/ x² = 34 .
hence proved !!!
hope it helps you dear !!
thanks !!
Answered by
0
Answer:
given,
now,
finally,
hence proved
Similar questions
History,
9 months ago
English,
9 months ago
Math,
1 year ago
Chemistry,
1 year ago
Social Sciences,
1 year ago